Příprava a optimalizace elektricky zvlákňovaných materiálů vhodných jako generátory elektrické energie - Pokorná, Romana (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2022)
Tato diplomová práce se zabývá energy harvestingem a je rozdělena na dvě části: teoretickou a praktickou. V teoretické části práce jsou nejprve popsány dielektrické parametry, je vysvětlen význam piezoelektrického a triboelektrického jevu a jsou představeny a popsány principy zisku elektrické energie. Poslední kapitola teoretické části práce je věnována různým elektricky zvlákňovaným materiálům vhodných pro energy harvesting. Praktická část práce je zaměřena na nanovlákna jakožto generátory energie. Právě v této části jsou proměřeny vybrané dielektrické parametry: dielektrická konstanta (relativní permitivita) a ztrátový činitel. Dále je vyroben funkční triboelektrický nanogenerátor a jsou proměřeny jeho vlastnosti.

This master's thesis is focused on energy harvesting and is divided into two parts: theoretical and practical part. The theoretical part of the thesis contains the dielectric parameters, the meaning of the piezoelectric and triboelectric effect and the principles of electric energy gain in energy havesting. The last chapter of the theoretical part is devoted to various electrospun materials suitable for energy harvesting. The practical part of the work deals with nanofibers as an energy generator and describes their dielectric parameters. In this part the relative permittivity and loss factor of selected types of nanofibers are measured. Also the triboelectric nanogenerator is made and it's properties are measured.
Preparation and optimization of electrospun materials suitable as electricity generators
Keywords: Energy harvesting; nanovlákna; piezoelektrický jev; triboelektrický jev; dielektrická konstanta (relativní permitivita); ztrátový činitel; triboelektrický nanogenerátor (TENG); Energy harvesting; nanofibers; piezoelectric effect; triboelectric effect; dielectric constant (relative permittivity); dielectric dissipation factor; triboelectric nanogenerator (TENG)